Correlation and regression model of medical clinic quality indicators through ISO 9001:2015 and ISO 7101:2023 standards (Texas Journal of Engineering and Technology, 2026)
In this article, quality indicators were studied based on international standards ISO 9001:2015 and ISO 7101:2023, and an empirical-statistical analysis was conducted based on the identified quality indicators. The identified model was tested for adequacy based on Student’s and Fisher’s criteria. The identified regression equation was confirmed by statistical analysis (Fisher F-criterion p < 0.001) and high determination coefficients (R2 > 0.94). The models were constructed based on Student’s t-test, and the statistical significance of all regression coefficients was determined. The results of the empirical-statistical analysis show that the application of the requirements of the ISO 9001:2015 and ISO 7101:2023 standards have a direct impact on the determining changes in the quality of medical laboratory services. The identified quality indicators and mathematical models can be applied in other medical laboratories.